-6p-4q=10

Simple and best practice solution for -6p-4q=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6p-4q=10 equation:


Simplifying
-6p + -4q = 10

Solving
-6p + -4q = 10

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '4q' to each side of the equation.
-6p + -4q + 4q = 10 + 4q

Combine like terms: -4q + 4q = 0
-6p + 0 = 10 + 4q
-6p = 10 + 4q

Divide each side by '-6'.
p = -1.666666667 + -0.6666666667q

Simplifying
p = -1.666666667 + -0.6666666667q

See similar equations:

| 4y^2+16y+4=0 | | G-g+2g=20 | | 8y+12x+1=30 | | 26i=50 | | 11u-6u-3u-2u+2u=14 | | 4x^2+5.11x-0.11=0 | | 4x^22+5.11x-0.11=0 | | 29-(8)1.5x+12x+1=30 | | 24=3/4w | | 15+(32n)=828 | | -y+2z=5 | | 8x^2-16x-18=6 | | 15+(32n)=207 | | 0.01x+0.05=0.08 | | 6q^2-43q-40=0 | | 18b-18b+3b-2b=8 | | -100x^2+55x+3=50x^2-55+23 | | 7(4k+3)+(6k-8)=145 | | 3x+0.05=0.26 | | 4a+12=6a | | 9x^2+18x-20=7 | | 5(x+6)-30=-2(x-4)+20 | | 0=-3x^2+30x-46 | | 96=8v | | -5x+4=2(3-x) | | x^2+19x+75=0 | | x^2+6x-18=9 | | (x1,y1)=(1/2,-1) | | 169.06=28.74 | | 3.6*10^-10/9*10^-6 | | x^2+2x-16=-8 | | x/4-9=-20 |

Equations solver categories